Reaksi pasar modal Indonesia terhadap peristiwa virus Corona - Khaulis nia hidayah Khaulis (Jurnal Investasi Islam, 2020)
This research uses the event study analysis method (evet study), the research period used for 44 days with the observation period used in this study is t-3 (the day before the announcement) and t + 3 (the day after the announcement) coronavirus events enter Indonesia. The sample in this study focused on the CSPI during the observation period in the form of daily stock price closing data. The events examined were non-economic events, namely the Coronavirus or covid 19 that affected the capital market. The population in this study are all companies listed on the IDX on the LQ45 index. The sampling technique in this study uses accidental sampling. In accidental sampling that is the determination of samples based on coincidence or anyone who happens to meet with researchers can be used with samples and sampling is not determined in advance, so researchers simply collect data from sampling units that are met or already exist.